PARTISIPASI PELANGGAN, ANTESEDEN DAN PENGARUHNYA TERHADAP KUALITAS JASA: PERSPEKTIF SERVICE-DOMINANT LOGIC - Dwinita Laksmidewi (Jurnal Manajemen, 2014)
This paper studies customers as active participants in service encounter. Based on Service-Dominant Logic perspective, this paper discusses previous research related to antecedents of customer participation, and its effect on service quality. The author reveals that there is an inconsistency in previous research, the customer participation has a positive effect or otherwise negatively affect the perceived service quality. The author proposes some proposition that perceived service risk, customer readiness, and perceived control are antecedents of customer participation. Further, the author proposes that the effect of value creation on service quality is moderated by customer culture and organizational culture.